Elastic wave propagation simulation in the presence of surface topography - Tessmer, Ekkehart; Kosloff, Dan; Behle, Alfred (Geophysical journal international, 1992)
We present a 2-D numerical modelling algorithm based on a pseudo-spectral method which accounts for surface topography. The modelling scheme uses Fourier derivative operators for spatial differencing in the horizontal direction, whereas a Chebyshev operator is used for vertical derivatives. The incorporation of surface topography is achieved by mapping a rectangular grid onto a curved grid. Modelling of surface topography is important to study near-surface effects of wave propagation in field seismic situations, since diffraction and scattering at rough surfaces are non-ray effects and can only be understood as wave phenomena. Static corrections cannot always account for these effects and some care has to be taken in their interpretation. The presented modelling algorithm can serve as a powerful tool for the study of wave propagation phenomena in the vicinity of non-planar surfaces or interfaces.